Microbiota modulation and effects on metabolic biomarkers by orange juice: a controlled clinical trial - Fidélix, Melaine [UNESP]; Milenkovic, Dragan; Sivieri, Katia [UNESP]; Cesar, Thais [UNESP] (Royal Society of Chemistry (RSC), 2020)
The impact of habitual orange juice consumption on microbiota, lipid and sugar metabolism was investigated in a controlled clinical trial. The clinical procedure is as follows: ten women who had a regular diet without orange juice for 30 days (OJ-free diet), followed by a regular diet plus 300 ml d-1 orange juice for 60 days (OJ-Diet), and 30 days with a regular diet without orange juice (Washout). Biochemical and dietary parameters were monitored, and blood, urine and stool samples were collected every 30 days until the end of the study. Hesperidin and naringin metabolites in the urine were identified by UHPLC, and the microbiota composition of the feces was determined by 16S rRNA. At the end of the OJ-Diet, there was a reduction in glucose (-6.5%), insulin (-33%), insulin resistance (-44%), LDL-C (-16%) and triglycerides (-30%). After the washout, these parameters returned to their initial values. There were no changes in the body weight or fat during the experimental time. The intestinal bacteria, Lactobacillus spp., Akkermansia spp., and Ruminococcus spp., increased after the intervention with orange juice. In addition, an inverse correlation was detected between these bacteria and glycemia, insulin, HOMA-IR, triglycerides, total cholesterol and LDL-C, but a direct correlation with HDL-C. In conclusion, orange juice showed a prebiotic effect, modulating the intestinal microbiota while improving the glycemia and lipid profiles.